Numerical Experiments to Obtain the Scaling Laws for Neutron Yield on Mather-Type Plasma Focus Machines Below 500 Joules - Arwinder, Singh*; Lee, S.; Saw, S. H. (Kathmandu University, 2014)
In this paper, we explain how we have fitted Lee‘s 5-phase and 6-phase model code to analyze the current waveforms of 6 small plasma focus machines (below 500Joules) working in deuterium gas medium. Using the information from the codefitted to these current waveforms, the scaling laws for these small- energy machines were obtained as follows